Investigation of inversion, accumulation and junctionless mode bulk Germanium FinFETs. (November 2017) - Thirunavukkarasu, Vasanthan; Lee, Jaehyun; Sadi, Toufik; Georgiev, Vihar P.; Lema, Fikru-Adamu; Soundarapandian, Karuppasamy Pandian; Jhan, Yi-Ruei; Yang, Shang-Yi; Lin, Yu-Ru; Kurniawan, Erry Dwi; Wu, Yung-Chun; Asenov, Asen
Abstract: The characteristic performance of n-type and p-type inversion (IM) mode, accumulation (AC) mode and junctionless (JL) mode, bulk Germanium FinFET device with 3-nm gate length (LG ) are demonstrated by using 3-D quantum transport device simulation. The simulated bulk Ge FinFET device exhibits favorable short channel characteristics, including drain-induced barrier lowering (DIBL<10 mV/V), sub threshold slope (SS∼64mV/dec.). Electron density distributions in ON-state and OFF-state also show that the simulated devices have large ION /IOFF ratios. Homogenous source/drain doping is maintained and only the channel doping is varied among different operating modes. Also, a constant threshold voltage |VTH | ∼ 0.31 V is maintained. Moreover, the calculated quantum capacitance (CQ ) values of the Ge nanowire emphasizes the importance of quantum confinement effects (QCE) on the performance of the ultra-scaled devices. Highlights: Quantum confinement effects will influence performances of ultra-scaled nano-devices. Especially, the band diagram, valley-splitting in different sub-bands, charge distribution in different valleys, density of states and effective mass will determine the characteristics of devices. Junctionless Ge Transistors will provide the optimum device performance in scaled dimensions.